Legal Analysis Of Marine Inspector's Duties and Responsibilities in Conducting Ship's Seaworthiness Tests : Research Study on Batam Special KSOP - Meilen Yudi Lumantow; Soerya Respationo; Bachtiar Simatupang; Erniyanti Erniyanti (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
The importance of the role of Marine Inspectors in ensuring the safety and security of shipping through ship seaworthiness tests, which are regulated in various laws and regulations. However, the implementation of the duties and responsibilities of the Marine Inspector at the Batam Special KSOP still faces various obstacles that affect the effectiveness and efficiency of ship inspections. The purpose of this study is to analyze juridically the duties and responsibilities of the Marine Inspector in conducting a shipworthiness test at the Batam Special KSOP, identify the obstacles faced, and provide suggestions to overcome these obstacles. The research method used is a normative juridical method with an analytical descriptive approach, which involves the study of legal documents, as well as empirical juridical with case analysis, and interviews with related parties at the Batam Special KSOP. The results of the study show that Marine Inspectors at the Batam Special KSOP have a very crucial role in maintaining shipping safety, but they face significant obstacles such as limited human resources and equipment, lack of continuous training, and suboptimal coordination between agencies. Low compliance from ship owners and operators is also a major challenge in carrying out their dutie. Suggestions for addressing these obstacles include increasing the number and competence of Marine Inspectors through ongoing recruitment and training, investing in modern equipment and digital technology, and improving inter-agency coordination through the establishment of regular coordination forums. In addition, strict law enforcement against violations of safety standards and increased education and socialization to ship owners and operators are expected to increase compliance and awareness of the importance of shipping safety. With the implementation of these measures, it is hoped that Marine Inspectors can carry out their duties more effectively, so that the safety and security of shipping in Batam City can be guaranteed and improved.